The concept of revelation in terms of the evolution of consciousness - Nürnberger, Klaus (HTS teologiese studies, 2016)
Following Paul’s injunction in 1 Corinthians 9:19–23 we have to ‘become scientists’ to a scientifically informed audience. While theology cannot agree with the naturalist denial of transcendence, it can adopt the experiential-realist approach typical for the sciences in its description of the Christian faith as an immanent part of cosmic evolution, albeit at a higher level of emergence. The article begins with my understanding of evolutionary theory (big bang cosmology, entropy, emergence, neural networks as infrastructure of consciousness, evolution and differentiation, sequences of past, present and future, contingency etc.) It then describes God consciousness as the intuition, perception or conceptualisation of the transcendent Source and Destiny of experienced reality and locates God consciousness in the evolutionary process. Biblical God consciousness displays two distinct characteristics: God’s creative power is experienced in reality, while God’s benevolent intentionality is proclaimed on the basis of a religious tradition. The evolutionary trajectory of biblical God consciousness, culminating in the Christ-event, is sketched and the God consciousness of Jesus is deduced from its religious embeddedness, its social-environmental relationships and its religious impact. Implications of an experiential-realist approach are (1) a dynamic, rather than ontological Christology and (2) the cosmic significance of the sacrifice of God in Christ. On this basis revelation is described first in experiential-realist and then in theological terms. The tension between the experience of God’s creative power and the proclamation of God’s benevolence leads to a dynamic, rather than ontological rendering of the Trinity. Finally, traditional eschatological assumptions are reconceptualised as God’s dynamic vision of comprehensive well-being operating like a horizon that moves on as we approach it and displays ever new vistas, challenges and opportunities.